MicroRNA‐125b suppressesed human liver cancer cell proliferation and metastasis by directly targeting oncogene LIN28B2 - Liang, Linhui; Wong, Chun‐Ming; Ying, Qiao; Fan, Dorothy Ngo‐Yin; Huang, Shenglin; Ding, Jie; Yao, Jian; Yan, Mingxia; Li, Jinjun; Yao, Ming; Ng, Irene Oi‐Lin; He, Xianghuo (Hepatology (Baltimore, Md.), 2010)
MicroRNAs (miRNAs) are small, noncoding RNAs that can act as oncogenes or tumor suppressors in human cancer. Our previous study showed that miR‐125b was a prognostic indicator for patients with hepatocellular carcinoma (HCC), but its functions and exact mechanisms in hepatic carcinogenesis are still unknown. Here we demonstrate that miR‐125b suppressed HCC cell growth in vitro and in vivo. Moreover, miR‐125b increased p21Cip1/Waf1 expression and arrested cell cycle at G1 to S transition. In addition, miR‐125b inhibited HCC cell migration and invasion. Further studies revealed that LIN28B was a downstream target of miR‐125b in HCC cells as miR‐125b bound directly to the 3′ untranslated region of LIN28B, thus reducing both the messenger RNA and protein levels of LIN28B. Silencing of LIN28B recapitulated the effects of miR‐125b overexpression, whereas enforced expression of LIN28B reversed the suppressive effects of miR‐125b. Conclusion: These findings indicate that miR‐125b exerts tumor‐suppressive effects in hepatic carcinogenesis through the suppression of oncogene LIN28B expression and suggest a therapeutic application of miR‐125b in HCC. (HEPATOLOGY 2010)